A Literature Review: Microsoft Word in Improving Writing Skill during Hybrid Learning - Yulanda, Eny Pricilia (Jurnal Penelitian Mahasiswa Indonesia, 2023)
The use of ICT in education is very dominating and plays an important role. Especially in learning the English Language, the existence of ICT makes it easier for teachers to teach English skills to all students. One kind of tool that supports the progress of language learning for students is Microsoft 365. These tools can be applied in English language learning because it is easier to get and share information. There are many types of Microsoft 365 tools to improve English skills, one of those is Microsoft Word. Microsoft word is software to make it easier for students to write and develop their creativity in writing. Therefore, the author wants to see how the impact of using an application. This research provided a literature review of previous studies in Microsoft Word from Microsoft 365 on English language learning. There are two results after reviewing previous studies namely positive impacts and negative impacts.